2010
DOI: 10.1016/j.visres.2010.07.008
|View full text |Cite
|
Sign up to set email alerts
|

The human pupil and the use of video-based eyetrackers

Abstract: Video-based devices for measuring gaze direction are widespread. However, there is a built-in imprecision in such devices in the event that pupil diameter changes during the experiments. Data are presented to demonstrate this effect. The possibility of correcting eye-position records for the imprecision is discussed and preliminary examples of such correction are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 1 publication
5
79
1
Order By: Relevance
“…The absolute magnitude of fixation disparity was significantly greater in the EyeLink data set than in the DPI data set and, therefore, fewer fixations were classed as aligned. Wyatt (2010) demonstrated that changes in pupil size can affect the accuracy of camera-based eyetrackers. Drewes, Masson, and Montagnine (2012) demonstrated a method to compensate for this artifact by calibrating during constricted and dilated pupil conditions, using pupil size as an index to weight the calibrations.…”
Section: Discussionmentioning
confidence: 99%
“…The absolute magnitude of fixation disparity was significantly greater in the EyeLink data set than in the DPI data set and, therefore, fewer fixations were classed as aligned. Wyatt (2010) demonstrated that changes in pupil size can affect the accuracy of camera-based eyetrackers. Drewes, Masson, and Montagnine (2012) demonstrated a method to compensate for this artifact by calibrating during constricted and dilated pupil conditions, using pupil size as an index to weight the calibrations.…”
Section: Discussionmentioning
confidence: 99%
“…The signals coming from PD recordings have been analyzed in both the time and frequency domains: State-of-the art is briefly reviewed in this section. Regardless of the method employed for the analysis, eye-blink artifacts represent a common problem in video-pupillography: Most systems measure pupil size upon eye image processing (see Holmqvist et al, 2010;Wyatt, 2010). During eye-blinks the lid covers the eye, and the camera cannot detect the pupil.…”
Section: Methods For Pd Data Analysismentioning
confidence: 99%
“…However, the spatial error in eye position measuring can vary greatly within trials depending on physiological and cognitive factors, as well as the participant's compliance during the task. For example, it has been shown that the measured gaze position using video-based eyetrackers is influenced by the size of the pupil (Drewes, Masson, & Montagnini, 2012;Wyatt, 2010), which, in turn, depends on the stimulus luminance, which might vary between and within trials but can also be influenced by task difficulty or cognitive load (e.g., Beatty, 1982;Granholm, Asarnow, Sarkin, & Dykes, 1996;Hess & Polt, 1964). The radius of the scotoma should thus be increased by the averaged spatial error of the eye-tracking system, which should be separately measured-for example, via fixation validation, as in our experiment.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%